Impacts of foreign currency exposure on Malaysia’s firm value: Firm value, hedging and corporate governance perspectives - Yam, Roselene Sou Cheng; Ei, Yet Chu; Song, Saw Imm; Lai, Tian So (Universal Publishers, 2017)
Purpose: This study examines and assesses the relationship between foreign currency exposures in terms of account receivable and payable and firm value of Malaysia firms. Design/methodology/approach: The study takes the balance sheet approach where a total sample firm of 148 Malaysia public reported their foreign currencies exposure from 2006 to 2013. Foreign currencies exposures in USD and SGD are regressed on firm value as these are most reported foreign currencies exposures. The study examines the issues from the perspective of firms’ size, hedging strategy, and corporate governance perspective. Findings: The findings suggest that Malaysia firms do not manage their exposures to USD well, both account payable and receivable. Large firms are also not well equipped to improve firm value when it is highly exposed, especially to USD as compared to SGD. Hedging strategies are not effective in the country as it does not significantly improve firm value. However, the presence of independent directors and large shareholders assert some monitoring effects on USD payables exposures and SGD receivable exposures, which lead to a positive firm value. Research limitations/implications: Corporate governance could substitute the role of hedging strategy in managing foreign currencies exposures. The research is hindered by the limitation information on hedging reported in annual reports. Practical implications: The study suggests the role of corporate governance is essential in various perspective of financial management. Large shareholders and independent directors could assert an effective role in monitoring risk as their controlling stake increases. In terms of USD exposures, which is more volatile, Malaysia firms are not managing USD exposures well and lead to declining of firm value. Malaysia firms should be more prepared financially and strategically when dealing with USD exposure, which is more volatile. Originality/value: The study applies balance sheet approach based on account payable and receivable on currencies exposure. Various perspective, especially issues on corporate governance is new when approaching the issues of foreign currencies exposures, especially in the contexts of emerging economy.